The Impact of Teachers' Leadership Styles on Students' Engagement in a Private School in the Emirate of Abu Dhabi - WATTAR, MAYA MOHAMMAD MAMOUN AKKAD (2025)
“Within every school there is a sleeping giant of teacher leadership, which can be a strong catalyst for making change. By using the energy of teacher leaders as agents of school change, the reform of public education will stand a better chance of building momentum” Marilyn Katzenmeyer & Gayle Moller (2001, p.2). The study aimed to identify the teacher's leadership style which showed giant effects on students’ engagement level in a private school in Abu Dhabi. The study aimed to identify teachers’ leadership styles that influence the key success of any learning process which is engagement. Respectively, the study aimed to answer the following main question: 1. What are the most effective teacher leadership styles which affect students’ engagement during the lessons? To answer this main question, two sub questions were asked: 1) To what extent does a teacher's leadership styles affect students’ engagement? 2)What are the relationships between different teacher leadership styles (e.g., transformational, transactional, dominant) and students' levels of engagement, as measured by their attention, participation, and motivation during class activities? This research employed a qualitative method of data gathering where both interviews and observations were conducted to collect data. Teachers of different subjects from grade 1 to 5 were observed during their whole lessons.